PELAKSANAAN PENGAWASAN LALU LINTAS ANGKUTAN JALAN (LLAJ) DI KOTA PEKANBARU (Studi Pada Angkutan Travel Luar Kota dan Dalam Kota) - ", Fariswadi; Tua, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The research was conducted in the city of Pekanbaru is the Department of Transportation Traffic Monitoring the Implementation of Transportation (LLAJ) in Pekanbaru City (Studies in Urban and Transport Traveling Outside In The City) The aim is to determine how the Implementation Monitoring Traffic Transportation (LLAJ) in the city of Pekanbaru (study On Transportation Travel Outside the City and in the City), The purpose of this study is to investigate the implementation of the Road Traffic and Transport Supervision (LLAJ) in the city of Pekanbaru (Studies in the Outer City Travel and Transportation in the City) and the factors that affect the implementation of the Road Traffic and Transport Supervision (LLAJ) in the city of Pekanbaru (Studies in Out of Town Travel and Transportation in the City). The method used in this study is the type of data collected included primary data is data that was obtained directly from the informant that wasdal Head, ed wasdal, PO, and the people who became the object of research in the form of information that is relevant to the issues formulated in the research . Include: such as interviews, observation or written remarks. As well as secondary data includes data ie the data that was obtained from the documents and reports that are related to the research problem and also books related to this research. While the data clotting techniques used were interviews, observation and study of literature and. Techniques of data analysis in this study performed using data processed using qualitative methods where the data obtained from the interview onwards systematically described with reference to the theoretical foundation or government regulations relating to the discussion to find solutions to problems. From these results it can be concluded that the implementation of Transportation Traffic Monitoring (LLAJ) in Pekanbaru City (Studies in Urban and Transport Traveling Outside In The City). still not running as expected or can not be considered successful as expected, it is evident from the respondents or the public. As for the implementation of monitoring indicators that set standards, conduct assessments and perform corrective actions. Keywords : implementation, transportation, travel